2011
DOI: 10.3168/jds.2010-3623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactic acid bacteria inoculant and beet pulp addition on fermentation characteristics and in vitro ruminal digestion of vegetable residue silage

Abstract: The objective of this study was to determine the effect of beet pulp (BP) and lactic acid bacteria (LAB) on silage fermentation quality and in vitro ruminal dry matter (DM) digestion of vegetable residues, including white cabbage, Chinese cabbage, red cabbage, and lettuce. Silage was prepared using a small-scale fermentation system, and treatments were designed as control silage without additive or with BP (30% fresh matter basis), LAB inoculant Chikuso-1 (Lactobacillus plantarum, 5mg/kg, fresh matter basis), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
91
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 21 publications
20
91
1
1
Order By: Relevance
“…The negative effect of fiber on digestibility is well known, and lignin is the component most negatively associated with fiber digestion by ruminants (Jung and Allen, 1995); this helps us to understand the obtained results. Our results are in agreement with those reported by Cao et al (2011), who found increases in DM digestibility of Chinese cabbage silages treated with beet pulp.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The negative effect of fiber on digestibility is well known, and lignin is the component most negatively associated with fiber digestion by ruminants (Jung and Allen, 1995); this helps us to understand the obtained results. Our results are in agreement with those reported by Cao et al (2011), who found increases in DM digestibility of Chinese cabbage silages treated with beet pulp.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the commercial processing of vegetables in the world results in many residues, which are a waste of resources that leads to possible environmental problems because of unsuitable disposal (Cao et al, 2011). Thus, considering that approximately 45% of the cabbage production is wasted or lost during cultivation in the field before human consumption (FAO, 2011), we investigated the possibility of ensiling cabbage treated with ground corn and a silage inoculant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers (Cao et al, 2011;Fang et al, 2012) found that LAB inoculants showed little effects on IVDMD, ruminal VFA concentration though they improved fermentation quality of napier grass (Pennisetum purpureum), rice straw and vegetable residue silages. Although IVDMD was not affected, in the present study, VFA production was increased in the treated silages in comparison to the untreated control, and such result implicate that nutrients of the drooping wild ryegrass were partially utilized during ensiling, and the fermentable organic matter left in the silages could be further metabolized by rumen microbes due to the application of additives during ensiling.…”
Section: Discussionmentioning
confidence: 99%